Sociodemographic predictors of occupational stress and exposure to workplace psychosocial hazards in a sample of Nigerian primary school teachers: Implications for career counselors - Ede, Moses Onyemaechi; Okeke, Chinedu Ifedi (Universitas Negeri Padang, 2023)
Teachers’ responsibilities are becoming increasingly challenging and demanding. This cross-sectional survey examined the demographic predictors of occupational stress and exposure to workplace psychosocial hazards among 254 primary school teachers. Two measurement tools were used to assess work-related stress and attendant psychosocial risks. Descriptive statistics and bivariate correlation analysis were employed to analyze the demographic characteristics of the participants and explore the relationships between these demographic factors, work-related stress, and psychosocial risks. The findings revealed a strong positive association between gender and teachers’ occupational stress. Additionally, working status, gender, and location showed a positive correlation with increased exposure to occupational psychosocial hazards among primary school teachers. Conversely, qualifications exhibited a negative and significant association with teachers’ exposure to psychosocial hazards at work. In conclusion, this study highlights a substantial increase in occupational stress for primary school teachers as they age and become more qualified. These findings suggest the need for educational policymakers in Nigerian school settings to address age, location, and working status discrimination to improve teachers’ well-being.